The furniture of Heaven & other parables for pilgrims - Mason, Mike, 1952-; DeVelasco, Joe (Wheaton, Ill. : H. Shaw, 1989)
Twenty-two short stories with a moral.
Keywords: Christian life -- Fiction; Short stories; Parables